2018
DOI: 10.3390/molecules23071819
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Heart Failure: A Promising Therapeutic Strategy?

Abstract: Heart failure is a multifactorial clinical syndrome characterized by the inability of the heart to pump sufficient blood to the body. Despite recent advances in medical management, poor outcomes in patients with heart failure remain very high. This highlights a need for novel paradigms for effective, preventive and curative strategies. Substantial evidence supports the importance of endogenous melatonin in cardiovascular health and the benefits of melatonin supplementation in various cardiac pathologies and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 142 publications
(247 reference statements)
0
43
0
2
Order By: Relevance
“…Both MTNR1A (MT1) and MTNR1B (MT2) are present in human brown tissue adypocytes indicating a possible involvement of MTNR1B in adipocyte physiology (106). A study investigating mechanisms regulating hibernation in European hamster (Cricetus cricetus) reported altered gene expression of MTNR1B (named MT2) in brown adipose tissue during the hibernation cycle (107). Daily rhythmicity with higher expression during the day were observed for mtnr1a and mtnr1d in the liver of rabbitfish (Signatus guttatus) which is involved in the maintenance of lipid homeostasis (92,93).…”
Section: Day/night Tissue Expression Of Melatonin Receptors In Femalementioning
confidence: 99%
“…Both MTNR1A (MT1) and MTNR1B (MT2) are present in human brown tissue adypocytes indicating a possible involvement of MTNR1B in adipocyte physiology (106). A study investigating mechanisms regulating hibernation in European hamster (Cricetus cricetus) reported altered gene expression of MTNR1B (named MT2) in brown adipose tissue during the hibernation cycle (107). Daily rhythmicity with higher expression during the day were observed for mtnr1a and mtnr1d in the liver of rabbitfish (Signatus guttatus) which is involved in the maintenance of lipid homeostasis (92,93).…”
Section: Day/night Tissue Expression Of Melatonin Receptors In Femalementioning
confidence: 99%
“…Osteoporosis and several other diseases increase in prevalence with age, simultaneous with the age-related drop in peak nocturnal melatonin secretion. Several articles have confirmed that this coincidence is not accidental, with the loss of melatonin being related to aggravation or an increase in the incidence of the ailment [13,169]. Thus, during aging, the drop in the nocturnal melatonin peak is associated with a rise in bone resorption, suggesting that melatonin may act as an endogenous osteoclast inhibitor [178].…”
Section: Apoptosismentioning
confidence: 99%
“…Heart failure is also a multifactorial syndrome that increases in prevalence with age [169]. Heart failure involves cardiomyocyte apoptosis; this is a major physiopathological feature and melatonin reverses it [56,167,179,[281][282][283].…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Another attribute of melatonin which makes it special among other antioxidants is that while interacting with free radicals it does not turn into a prooxidant by losing an electron. [6][7][8] In current literature, there are many studies revealing the cardioprotective effect of melatonin [9][10][11][12] alongside its therapeutic effects on several other diseases. Simko et al 10 showed that melatonin administration significantly treated hypertension and increased oxidative stress in left ventricle and aorta, left ventricular hypertrophy, and fibrosis caused by continuous exposure to light.…”
Section: Introductionmentioning
confidence: 99%